2019
DOI: 10.2147/ott.s201052
|View full text |Cite
|
Sign up to set email alerts
|

<p>m<sup>6</sup>A methyltransferase METTL3 suppresses colorectal cancer proliferation and migration through p38/ERK pathways</p>

Abstract: Purpose: Although many biological processes are involved in the modification of N 6 -methyladenosine (m 6 A), the exact role of m 6 A in the development of malignant tumors remains unclear. Methyltransferase 3 (METTL3) is a major RNA N 6 -methyladenosine methyltransferase. We aimed to explore the role of METTL3 in colorectal cancer (CRC) carcinogenesis and disease progression. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
118
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 19 publications
4
118
1
Order By: Relevance
“…Frontiers in Oncology | www.frontiersin.org colorectal cancer (26). Negative expression of METTL3 was significantly correlated with larger tumor size and metastasis.…”
Section: Mettl3 In Colorectal Cancermentioning
confidence: 92%
See 2 more Smart Citations
“…Frontiers in Oncology | www.frontiersin.org colorectal cancer (26). Negative expression of METTL3 was significantly correlated with larger tumor size and metastasis.…”
Section: Mettl3 In Colorectal Cancermentioning
confidence: 92%
“…In contrast, Deng et al showed that high expression of METTL3 was significantly associated with longer survival time and METTL3 played a tumor-suppressive role in colorectal cancer (26).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In CRC, a recent research has verified that METTL3 could promote cell self‐renewal, stem cell frequency and migration through an m6A‐IGF2BP2‐dependent mechanism . However, another study showed that METTL3 could suppress colorectal cancer proliferation and migration through p38/ERK pathways . Therefore, the role of METTL3 in CRC might be controversial and need to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…37 However, another study showed that METTL3 could suppress colorectal cancer proliferation and migration through p38/ERK pathways. 38 Therefore, the role of METTL3 in CRC might be controversial and need to be further explored. In our present study, we confirmed that METTL3 could promote CRC cells proliferation and revealed a new mechanism by directly regulating cyclin proteins in an m6A-dependent manner.…”
Section: Introductionmentioning
confidence: 99%